2021
DOI: 10.1186/s12934-021-01655-7
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of sago processing wastewater into biodiesel: Optimization of lipid production by an oleaginous yeast, Candida tropicalis ASY2 and its transesterification process using response surface methodology

Abstract: Background Biodiesel is an eco-friendly and renewable energy source and a valuable substitute for petro-diesel. Sago processing wastewater (SWW), a by-product of the cassava processing industry, has starch content ranging from 4 to 7 g L–1 and serves as an outstanding source for producing microbial lipids by the oleaginous microorganisms. In the present study, Candida tropicalis ASY2 was employed to optimize single-cell oil (SCO) production using SWW and subsequent transesterification by respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Microbial glycobiotechnology refers to sustainable bioprocesses for the bioconversion of carbohydrates through microbial enzymes and microbial technologies and the generation of tailor-made carbohydrate bioproducts/polymers for various novel applications in bioenergy and bioenergy fuels, biomaterials, in food and nutrition, and pharmaceuticals.This special issue is intended to present a special collection with a thematic scheme: Microbial Glycobiotechnology. Eighteen articles, connected to glycan biosynthesis, glycoenzymology, modification of complex carbohydrates and their corresponding glycoconjugates, including glycans, glycoproteins, glycolipids, biological functions of glycoconjugates and glycolipids, have been published there [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Editorialmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbial glycobiotechnology refers to sustainable bioprocesses for the bioconversion of carbohydrates through microbial enzymes and microbial technologies and the generation of tailor-made carbohydrate bioproducts/polymers for various novel applications in bioenergy and bioenergy fuels, biomaterials, in food and nutrition, and pharmaceuticals.This special issue is intended to present a special collection with a thematic scheme: Microbial Glycobiotechnology. Eighteen articles, connected to glycan biosynthesis, glycoenzymology, modification of complex carbohydrates and their corresponding glycoconjugates, including glycans, glycoproteins, glycolipids, biological functions of glycoconjugates and glycolipids, have been published there [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Editorialmentioning
confidence: 99%
“…In another study, Thangavelu et al [2] investigated the bioconversion potential of Candida tropicalis ASY2 to produce biodiesel from sago processing wastewater (SWW). They observed that the microbial lipids from C. tropicalis strain as alternative oil substitutes for sustainable biodiesel production.…”
Section: Bioenergy and Bioproductsmentioning
confidence: 99%
See 1 more Smart Citation
“…MTCC 5455 produces BD from Brassica juncea gives the highest FAME yield of 15% after 10 h of enzymatic reaction 58 . BD was derived from the oleaginous yeast Candida tropicalis ASY2 yielded a higher FAME of 86% at the optimized conditions 59 . Base‐catalyzed such as KOH transesterification is the favored method when compared to the other methods since it has softer reaction conditions, requires less time to complete, and is less expensive 60 .…”
Section: Resultsmentioning
confidence: 99%
“…58 BD was derived from the oleaginous yeast Candida tropicalis ASY2 yielded a higher FAME of 86% at the optimized conditions. 59 Base-catalyzed such as KOH transesterification is the favored method when compared to the other methods since it has softer reaction conditions, requires less time to complete, and is less expensive. 60 From the previous studies, it was proved that the oleaginous yeast can produce BD.…”
Section: Lipid and Bd Productionmentioning
confidence: 99%